Greening‐Induced Biophysical Impacts Lead to Earlier Spring and Autumn Phenology in Temperate and Boreal Forests - Jing Guo; Jinmei Wang; Yuxin Qiao; Xu Huang; Nicholas G. Smith; Zhiyong Liu; Rui Zhang; Xiuzhi Chen; Chaoyang Wu; Josep Peñuelas; Lei Chen (Earth's Future)
Abstract Tree phenology, the timing of periodic biological events in trees, is highly sensitive to climate change. Previous studies have indicated that forest greening can impact the local climate by modifying the seasonal surface energy budget. However, the understanding of tree phenological responses to forest greening at large spatial scales remains limited. Utilizing satellite‐derived phenological and leaf area index data spanning from 2001 to 2021, herein we show that forest greening led to earlier spring and autumn phenology in both temperate and boreal forests. Our findings demonstrated that forest greening during winter and spring contributed to a reduction in surface albedo, resulting in biophysical warming and consequently advancing spring leaf phenology. Conversely, forest greening in summer and autumn induced biophysical cooling through increased evapotranspiration, leading to an earlier onset of autumn leaf phenology. Our findings highlight the significant impact of forest greening‐induced local seasonal climate changes on shaping tree phenology in temperate and boreal forests. It is crucial to consider these greening‐induced alterations in microclimate conditions when modeling changes in tree phenology under future climate warming scenarios.